Unquiet Thoughts: Spenser, Scudamour, and John Dowland’s First Booke of Songes - Leach, EE (2012)
This current online version is a July 2012 redaction, correction, and updating of the pre-print edition of Elizabeth Eva Leach, “The Unquiet Thoughts of Edmund Spenser’s Scudamour and John Dowland’s First Booke of Songes” in “Uno gentile et subtile ingenio”: Studies in Renaissance Music in Honour of Bonnie Blackburn, edited by Gioia Filocamo and M. Jennifer Bloxam (Turnhout: Brepols, 2009), 513–20